2021
DOI: 10.3390/genes12081249
|View full text |Cite
|
Sign up to set email alerts
|

Proof of Gene Doping in a Mouse Model with a Human Erythropoietin Gene Transferred Using an Adenoviral Vector

Abstract: Despite the World Anti-Doping Agency (WADA) ban on gene doping in the context of advancements in gene therapy, the risk of EPO gene-based doping among athletes is still present. To address this and similar risks, gene-doping tests are being developed in doping control laboratories worldwide. In this regard, the present study was performed with two objectives: to develop a robust gene-doping mouse model with the human EPO gene (hEPO) transferred using recombinant adenovirus (rAdV) as a vector and to develop a d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…Western blotting reported in many papers shows different sizes and shapes of the bands compared with our bands [80][81][82][83][84][85]. The important part of the WADA recommendation is the use of the antibody clone AE7A5 [82].…”
Section: Deglycosylation-coupled Western Blottingmentioning
confidence: 60%
“…Western blotting reported in many papers shows different sizes and shapes of the bands compared with our bands [80][81][82][83][84][85]. The important part of the WADA recommendation is the use of the antibody clone AE7A5 [82].…”
Section: Deglycosylation-coupled Western Blottingmentioning
confidence: 60%
“…Typically, the injected transgenes (e.g., local injection to muscle tissue or systemic intravenous administration) could be detected in human plasma . Previous reports demonstrated that the transgene concentration in blood could be in the range around 0.1–1 × 10 3 copy/μL (i.e., 0.15–1.5 × 10 –15 M) after intramuscular injection of the target plasmid. , To mimic a GD scenario, four low concentrations of hEPO plasmids (0, 10 –16 , 10 –13 , and 10 –10 M) were spiked in human plasma and measured after direct RPA without pretreatment (Figure a). The whole assay took ∼40 min, including 20 min of RPA and 20 min for CasGDP detection.…”
Section: Resultsmentioning
confidence: 99%
“…Total RNA-Seq was performed to identify the novel RNA markers, that is, fluctuated expressions dependent on the blood storage period. The method was similar to procedures in our previous study [ 23 , 24 ]. Preparation of the libraries and NGS run was conducted at the Department of Sports Medicine in the Organization for Open Facility Initiatives, University of Tsukuba (Tsukuba, Ibaraki, Japan).…”
Section: Methodsmentioning
confidence: 99%